Gastronomy as a tourism attraction for Łódź - Stasiak, Andrzej (Turyzm/Tourism, 2015)
Over the last 25 years, a rapid development in gastronomic services in Łódź and other large Polish cities has been observed, as a result of a growing interest in good cooking both on the part of inhabitants and visitors (culinary tourism). The article is an attempt to describe the potential of gastronomic resources in Łódź as a possible basis for creating a new tourism product for the city. The paper presents a historical outline of Łódź gastronomy, the specificity of the local cuisine and its delicacies, the major culinary events, and the structure and location of gastronomic establishments at the beginning of the 21st c., as well as other elements which may be used to create an attractive offer for tourists.